EXPLORING ADOLESCENTS’ PARTICIPATION IN DECISION MAKING IN RELATED FOSTER CARE PLACEMENTS IN SOUTH AFRICA - Ulene Schiller (Social Work/Maatskaplike Werk, 2015)
Since the United Nations Convention on the Rights of the Child was adopted in 1989, children have a right to express their views and participate in matters concerning them. This aspect of participation is also encompassed in legislation in South Africa. The country has adopted a developmental social work approach after becoming a democratic nation in 1994 to guide social work service delivery on all levels. The purpose of this paper is to explore the participatory decision making experiences that adolescents have relating to their foster care placements. Against this background, the theoretical premise of the paper is based on the principles of participatory decision making. A qualitative research study was conducted in which thirty-five adolescents in related foster care placements across South Africa were interviewed. The responses of adolescents indicate that these young people in foster placements feel they are not sufficiently included in the decision making aspects related to welfare service delivery to them. This presents a challenge to developmental social work, which aims to be democratic, inclusive, and participatory. The paper concludes with discussing the implications of these findings for foster care in South Africa and recommends that adolescents should be taken seriously in matters concerning them.